2021
DOI: 10.1209/0295-5075/133/27001
|View full text |Cite
|
Sign up to set email alerts
|

Continuous photon Hall effect on metal surface

Abstract: The continuous photon Hall effect excited in a surface plasmon polariton system is proposed and realized theoretically, in which the parallel incident light illuminates the small ball nearing the surface. The scattering direction can be continually modulated in the large range of almost 180 degree by the elliptical polarization state of the incident light. The physical reason is displayed intuitively by the component waves interference principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…1(a)). When the incident light is circularly polarized, the illuminated notch can be thought as a rotational dipole [1,2,16,17], which is composed of two independent dipoles along two perpendicular directions, just as shown in fig. 1(a).…”
Section: Complete Control Theorymentioning
confidence: 99%
“…1(a)). When the incident light is circularly polarized, the illuminated notch can be thought as a rotational dipole [1,2,16,17], which is composed of two independent dipoles along two perpendicular directions, just as shown in fig. 1(a).…”
Section: Complete Control Theorymentioning
confidence: 99%
“…In fact, the angular momentum is not conserved when the incident light is converted into SPP waves. Recently, it is found that the asymmetric scattering of PSHE results from the component wave interference (CWI) of electric or magnetic dipoles 9 , 23 , 24 , and this interference effect of the elliptical polarized dipole results in the selective directional scattering.…”
Section: Introductionmentioning
confidence: 99%
“…The realization and application of surface plasma waveguide is of great significance because it is key to realize all-optical circuit, and it possesses unique advantages such as strong confinement, low bend loss and so on. Based on the understanding of component wave interference of incident light (CWI theory) 23 , 24 , we believe PSHE can be realized in the waveguide structure. Motivated by this consideration, we hope to realize PSHE in metal-air-metal plasmatic waveguides, which will be greater progress towards practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Another major explanation is wavevector matching [7,21]. Recently, it was found that the directionality of PHE results from the interference of component waves excited by incident light [22][23][24][25], which is the so-called component wave interference (CWI) theory. However, these experimental and theoretical works are mainly focused on surface waves.…”
mentioning
confidence: 99%
“…The physical mechanism can be explained by CWI theory [23][24][25]. According to CWI theory, the elliptically (including circularly) polarized incident light involves two component waves polarized along both vertical and transverse directions, respectively.…”
mentioning
confidence: 99%